Bottom-up renewal of the Swiss party system. Issue 3 (27th May 2019) - Bochsler, Daniel
ABSTRACT: The Swiss party system and the institutional rules guiding elections are an anchor of stability in Swiss politics. This article investigates recent change in cantonal elections, and analyses how electoral swings in cantonal elections diffuse to other cantons, and whether they predict future electoral swings in the national electoral arena. Empirically, the article combines a statistical analysis of electoral results from the period 1990–2017 in cantonal and national elections with a qualitative discussion of the period from 2014 to 2017.